DECISION TO PURCHASE OF WARDAH SKINCARE PRODUCTS VIEWED FROM CELEBRITY ENDORSEMENT, BRAND IMAGE, AND CONSUMER TRUST (CASE STUDY ON WARDAH SKINCARE USERS SAMI LUWES SURAKARTA) - Devi Yulianti; Istiatin Istiatin; Eny Kustiyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine the influence of celebrity endorsers, brand image, and trust in purchasing decisions for Wardah Skincare products in Sami Luwes Surakarta. The research design uses a quantitative descriptive method. The population is consumers who buy and use Wardah Skincare in Sami Luwes Surakarta. The sample is 100 people calculated by the unknown population formula and taken by purposive sampling. Linear regression test, t-test, and coefficient of determination were used to analyze the data. The result is celebrity endorsers, brand image, and trust each have positively and significantly affected the decision to purchase Wardah Skincare products at Sami Luwes Surakarta. Keywords: celebrity endorser, brand image, Trust, Purchase decision